2009
DOI: 10.4039/n09-040
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal parasitism of hemlock looper (Lepidoptera: Geometridae) eggs in eastern Canada

Abstract: A 2-year field study was conducted using sentinel traps to determine the seasonal distribution of the egg parasitoid (Hymenoptera) complex attacking hemlock looper, Lambdina fiscellaria (Guenée), throughout eastern Quebec and western Newfoundland. Hemlock looper populations remained low in all areas over the course of the study. Parasitism of eggs in sentinel traps was generally lower in fall than in spring. Trichogramma Westwood (Trichogrammatidae) as well as Telenomus flavotibiae Pelletier and an unidentifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, T. coloradensis still have a considerable egg retention capability during periods of host deprivation. Both field and laboratory studies have shown that egg retention before adult overwintering is one of the most important conditions for effective parasitism early in the season (Hébert et al., ; Carleton et al., , ; Legault et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, T. coloradensis still have a considerable egg retention capability during periods of host deprivation. Both field and laboratory studies have shown that egg retention before adult overwintering is one of the most important conditions for effective parasitism early in the season (Hébert et al., ; Carleton et al., , ; Legault et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Telenomus coloradensis Crawford (Hymenoptera: Platygastridae; formerly Scelionidae according to Sharkey, ), a common natural enemy of hemlock looper eggs in northeastern Canada (Pelletier & Piché, ), plays a significant role as biological control agent (Hébert et al., ). Telenomus coloradensis can attack hemlock looper eggs either in their pre‐diapause and early diapause phase in fall or during the post‐diapause phase in spring (Carleton et al., , ; Legault et al., ). Parasitism reaches high levels only during spring, but underlying mechanisms remain to be explored (Hébert et al., ; Carleton et al., , ; Legault et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telenomus flavotibiae Pelletier parasitized hemlock looper eggs in the autumn, Telenomus droozi Muesebeck parasitized eggs during the spring, and Telenomus coloradensis Crawford parasitized hemlock looper eggs in both autumn and spring, with the vast majority of parasitism by T . coloradensis occurring during the spring (Carleton et al., 2009). It remains unclear, however, whether all or only a subset of these parasitoid species can contribute to suppressing hemlock looper populations.…”
Section: Introductionmentioning
confidence: 99%